A Novel Method Linking Antigen Presentation by Human Monocyte-Derived Macrophages to CD8+ T Cell Polyfunctionality - Short, Kirsty R.; Grant, Emma; Vissers, Marloes; Reading, Patrick; Diavatopoulos, Dimitri; Kedzierska, Katherine (Frontiers in Immunology, 2013)
To understand the interactions between innate and adaptive immunity, and specifically how virally-infected macrophages impact T cell function, novel assays examining the ability of macrophages to present antigen to CD8+ T cells are needed. In the present study, we have developed a robust in vitro assay to measure how antigen presentation by human monocyte-derived macrophages (MDMs) affects the functional capacity of autologous CD8+ T cells. The assay is based on the polyfunctional characteristics of antigen-specific CD8+ T cells, and is thus called a Mac-CD8 Polyfunctionality Assay. Following purification of monocytes and their maturation to monocyte derived macrophages (MDMs), MDMs were pulsed with an antigenic peptide to be presented to CD8+ T cells. Peptide pulsed MDMs were then incubated with antigen-specific CD8+ T cells in order to assess the efficacy of antigen presentation to T cells. CD8+ T cell polyfunctionality was assessed by staining with mAbs to IFN-, TNF- and CD107a in a multi-colour intracellular cytokine staining (ICS) assay. To highlight the utility of the Mac-CD8 Polyfunctionality Assay, we assessed the effects of influenza infection on the ability of human macrophages to present antigen to CD8+ T cells. We found that influenza infection of human MDMs can alter the effector efficacy of MDMs to activate more CD8+ T cells with cytotoxic capacity. This has important implications for understanding how the virus-infected macrophages affect adaptive immunity at the site of infection.